200k views
2 votes
PLEASE ANSWER ASAP!!!

If f(x) = 2x + 3 and g(x) = −x + 6, use the graph to find the solution to the equation f(x) = g(x).

A) x = 1

B) x = 0

C) x = −3 or x = 0

D) x = −3 or x = 1

PLEASE ANSWER ASAP!!! If f(x) = 2x + 3 and g(x) = −x + 6, use the graph to find the-example-1

1 Answer

0 votes

Answer:

The answer to your question is A) x = 1

Explanation:

We know that f(x) = 2x + 3 and g(x) = -x + 6

But f(x) = g(x)

Then, 2x + 3 = - x + 6

2x + x = 6 - 3

3x = 3

x = 3/3

x = 1

The solution is circle in the graph below.

PLEASE ANSWER ASAP!!! If f(x) = 2x + 3 and g(x) = −x + 6, use the graph to find the-example-1
User Sumit Bhatt
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.